High-Efficient Production of Adipose-Derived Stem Cell (ADSC) Secretome Through Maturation Process and Its Non-scarring Wound Healing Applications - An, Young-Hyeon; Kim, Dae Hyun; Lee, Eun Jung; Lee, Dabin; Park, Mihn Jeong; Ko, Junghyeon; Kim, Dong Wook; Koh, Jiwan; Hong, Hyun Sook; Son, Youngsook; Cho, Je-Yoel; Park, Ji-Ung; et al. (Frontiers in Bioengineering and Biotechnology, 2021)
Recently, the stem cell-derived secretome, which is the set of proteins expressed by stem cells and secreted into the extracellular space, has been demonstrated as a key contributor for tissue repair. In this study, we have produced two sets of high concentration secretomes from adipose-derived mesenchymal stem cells (ADSCs) that contain bovine serum or free of exogenous molecules. Through proteomic analysis, we elucidated that proteins related to extracellular matrix organization and growth factor-related proteins are highly secreted by ADSCs. Additionally, the application of ADSC secretome to full skin defect showed accelerated wound closure, enhanced angiogenic response, and complete regeneration of epithelial gaps. Furthermore, the ADSC secretome was capable of reducing scar formation. Finally, we show high dose injection of ADSC secretome via intraperitoneal or transdermal delivery demonstrated no detectable pathological conditions in various tissues/organs, which supports the notion that ADSC secretome can be safely utilized for tissue repair and regeneration.